Implementasi Pembelajaran Matematika Berdiferensiasi Di SMP Negeri 8 Medan - Rebika Afrina Br Simanjuntak; Renna Lania; Septina Simanihuruk; Ratna Soraya; Rosliana Siregar (Journal on Education, 2024)
This research aims to determine the impact of implementing differentiated learning and how it is implemented in class VII mathematics subjects at SMP Negeri 8 Medan. This type of research is qualitative research with student informants and subject teachers who have become Driving Teachers. The results of the research show that the implementation of differentiated learning has an impact on changes in students' behavior in learning, as can be seen from the results of observations that students are more active in learning activities and creative in carrying out tasks so that students' learning outcomes match the learning objectives. Meanwhile, the implementation of differentiated learning by teachers can respond to learning needs by paying attention to the preparation, implementation and assessment of differentiated learning. This research illustrates that the implementation of differentiated learning has an impact on good changes in student behavior and learning outcomes and the implementation of learning must be in accordance with the steps of differentiated learning.